Gastrointestinal Variables and Drug Absorption: Experimental, Computational and In Vitro Predictive Approaches - Bermejo, Marival (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book presents some of the state-of-the-art methods for the study of the gastrointestinal variables affecting oral drug absorption. Practical applications of new in vitro release/dissolution methods are presented, as well as in vitro permeability studies to explore segmental differences. The application of MRI methods for the study of colon physiology is presented to illustrate its potential applications in controlled release dosage form design. Some examples of successful in vitro-in vivo correlations show how implementing the gastrointestinal physiological variables in the new in vitro methods can improve the predictions of in vivo drug product performance. The book contains an updated review of the experimental, computational, and in vivo approaches for measuring intestinal permeability.